2009
DOI: 10.1029/2009ja014042
|View full text |Cite
|
Sign up to set email alerts
|

Kelvin‐Helmholtz waves at the Earth's magnetopause: Multiscale development and associated reconnection

Abstract: [1] We examine traversals on 20 November 2001 of the equatorial magnetopause boundary layer simultaneously at $1500 magnetic local time (MLT) by the Geotail spacecraft and at $1900 MLT by the Cluster spacecraft, which detected rolled-up MHDscale vortices generated by the Kelvin-Helmholtz instability (KHI) under prolonged northward interplanetary magnetic field conditions. Our purpose is to address the excitation process of the KHI, MHD-scale and ion-scale structures of the vortices, and the formation mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
182
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(205 citation statements)
references
References 100 publications
22
182
1
Order By: Relevance
“…The issue is therefore to understand where does reconnection occur: does it occur locally, within the vortex, as observed in other events reported in the literature (e.g. Nykyri et al, 2006;Hasegawa et al, 2009), or does it occur on a global scale, the reconnection site being far from the vortex? In Sect.…”
Section: Ions Electrons and Oxygen Kinetic Signatures In The Vorticesmentioning
confidence: 99%
See 1 more Smart Citation
“…The issue is therefore to understand where does reconnection occur: does it occur locally, within the vortex, as observed in other events reported in the literature (e.g. Nykyri et al, 2006;Hasegawa et al, 2009), or does it occur on a global scale, the reconnection site being far from the vortex? In Sect.…”
Section: Ions Electrons and Oxygen Kinetic Signatures In The Vorticesmentioning
confidence: 99%
“…Nishino et al (2007) analysed the ions and electrons distribution functions of a KH event and also interpreted their observations in terms of reconnection. Hasegawa et al (2009) identified reconnection signatures in a current sheet in the vortices.…”
Section: Introductionmentioning
confidence: 99%
“…Vorticity is expected in the magnetosheath due to, for example, reconnection along the dayside magnetopause (Lockwood and Smith 1992;Retinò et al 2007;Dunlop et al 2011) and along the flanks (Lin and Lee 1994), as well as due to velocity shear along the magnetopause/magnetosheath boundary (Hasegawa et al 2004;Hasegawa et al 2009). Figure 22 shows an interval of Cluster data when the spacecraft were in a high inclination orbit near apogee, just crossing the northern magnetopause and entering the magnetosheath.…”
Section: Electron Scale Turbulencementioning
confidence: 99%
“…These processes can trigger plasma transport and mixing within or at the edge of rolled-up KHVs. Decaying KHVs ultimately form a broad mixing layer at the dawn and dusk flanks (Nakamura et al 2006;Hasegawa et al 2009;Cowee et al 2009). …”
Section: Betatron and Stochastic Accelerationmentioning
confidence: 99%
See 1 more Smart Citation